Geospatial Analysis of Population Ageing in Bosnia and Herzegovina - Kadušić, Alma; Smajić, Sabahudin; Kunosić, Suad; Smajić, Nedima (Geographica Pannonica, 2023)
The aim of this research is to analyze the spatial distribution of the population ageing in Bosnia and Herzegovina and identify areas of the country that are particularly vulnerable to negative demographic trends. To achieve the goal of the study, data on the ageing coefficient and ageing index for the period 2013-2020 were used. The geospatial analysis of these indicators was performed using global (Global Moranʼs I and Getis-Ord General G) and local (Anselin Local Moranʼs I and Getis-Ord G*) indexes of spatial autocorrelation. The research results confirmed the clustering of both indicators. Ageing coefficient values are clustered in municipalities in western, northwestern, eastern, and central Bosnia and Herzegovina. Ageing index values are clustered in municipalities in central, western, northwestern, and northeastern Bosnia and Herzegovina. This study provides insight into the research methods of spatial demographic trends and phenomena, and its findings can serve as a basis for future demographic research and development in Bosnia and Herzegovina.